Synthesis of the 26-Membered Core of Thiopeptide Natural Products by Scalable Thiazole-Forming Reactions of Cysteine Derivatives and Nitriles - Johnson, Trevor C.; Christy, Mitchell P.; Siegel, Dionicio (Synthesis, 2020)
The increased resistance of bacteria to clinical antibiotics is one of the major dilemmas facing human health and without solutions the problem will grow exponentially worse. Thiopeptide natural products have shown promising antibiotic activities and provide an opportunity for the development of a new class of antibiotics. Attempts to directly translate these compounds into human medicine have been limited due to poor physiochemical properties. The synthesis of the core structure of the 26-membered class of thiopeptide natural products is reported using chemistry that enables the synthesis of large quantities of synthetic intermediates and the common core structure. The use of cysteine/nitrile condensation reactions followed by oxidation to generate thiazoles has been key in enabling large academic scale reactions that in many instances avoided chromatography further aiding in accessing large amounts of key synthetic intermediates.
Keywords: thiopeptide; natural product; thiazole; scalable; antibiotic; pharmacophore